Stories of physics teachers teaching special relativity concepts in senior high school - Nurahman, Arip; Kaniawati, Ida; Cahya Prima, Eka; Suhendi, Endi (Insitut Pendidikan Indonesia, 2024)
Teaching Special Relativity in senior high school presents significant challenges due to its abstract and counterintuitive concepts, which often contradict students’ everyday experiences. This study employs a narrative research approach to explore the experiences of three physics teachers in teaching Special Relativity. The findings reveal that teachers struggle with explaining relativistic effects such as time dilation, length contraction, and simultaneity, as students frequently hold persistent misconceptions influenced by classical mechanics and popular media. Furthermore, curriculum constraints and the lack of appropriate instructional resources hinder effective teaching. The study identifies key pedagogical strategies, including the use of interactive simulations, thought experiments, and historical contexts, to make relativity more accessible. Teachers emphasize the need for conceptual scaffolding before introducing mathematical derivations to ensure students grasp the fundamental principles. Despite the challenges, teachers express passion and excitement when students experience conceptual breakthroughs, highlighting the transformative power of physics education. This study underscores the importance of professional development programs and curriculum adjustments to better support teachers in delivering relativity concepts effectively. Future research should explore additional instructional interventions to enhance relativity education in high schools.